Magnetic slurry and preparation and application thereof
By using the combination of iron -based alloy powder with organic inorganic composite insulation and liquid resin and diluents in the magnetic slurry, the problem of uneven distribution of magnetic powder and cracking of inductances is solved. It is suitable for the production of high -frequency and miniature inductors.
Patent Information
- Application Number
- CN202411363291.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
AI Technical Summary
During the molding process, existing magnetic slurries are prone to cause uneven distribution of magnetic powder and inductance cracking, and the magnetic permeability is low, which cannot meet the requirements of conventional inductance sensing.
The iron -based alloy powder with organic inorganic composite insulation coverage is combined with the combination of liquid resin and dilute agent to form magnetic pulp. Surface insulation covering the iron -based alloy powder through inorganic insulators, surfactants, and organic covering resin to improve resistance and improve liquidity.
The problem of uneven distribution of magnetic powder and cracking of inductances, improve the magnetic guidance rate and insulation of magnetic pulp, so that it can work at 300V voltage, suitable for large -scale mass production.
Smart Images

Figure CN119361283A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a magnetic slurry and a preparation and application thereof. Background Art
[0002] Soft magnetic materials are widely used in the fields of automobiles, new energy, information, consumer electronics and power electronics due to their excellent comprehensive magnetic properties. With the development of electronic information technology, the performance requirements of soft magnetic materials are becoming higher and higher, and they are gradually developing towards high frequency and miniaturization.
[0003] The traditional production of power inductors requires winding, spot welding, cutting, molding, bending and other steps. Molding is to place the coil in a mold at room temperature, fill it with powder and mold it under high pressure. Due to the existence of external high pressure, the pressing process may damage the enameled copper wire. There are also problems such as cracking during the inductor curing process and uneven filling of magnetic powder.
[0004] Magnetic slurry can be applied to various microelectronic fields due to its excellent fluidity and magnetic properties. Through the compounding of various liquid resins and soft magnetic powders, magnetic powders are given fluidity, so as to adapt to molding under different conditions and meet the magnetic properties. After solidification, it becomes an inductor with high magnetic permeability and low magnetic loss. It can be used to make substrate embedded / embedded magnetic inductors, or other special shape inductors. It has excellent processing properties such as plugging holes and copper plating, and has high heat resistance and high reliability. The fluidity of magnetic slurry can avoid the cracking of enameled wires in the traditional molding process, and solve the problems of cracking during the solidification process and uneven filling of magnetic powder.
[0005] CN105647128A discloses a magnetic slurry and its preparation and application, wherein the magnetic slurry is composed of raw materials in the following mass ratio: 1 part of photothermal dual-curing resin, 1.5-4 parts of diluent, and 0.5-5 parts of magnetic powder; the photothermal dual-curing resin is an acrylic resin; the diluent has a boiling point of 80-180°C, a viscosity of 1-2mPa·s, a surface tension of 20-30mN / m, and is volatile; the magnetic powder particle size is 0.1-1μm. The magnetic slurry provided by this technical solution uses photothermal dual-curing resin as a curing matrix, and thermal curing can be used to compensate for the inability to deeply cure due to light scattering, refraction, and absorption of fillers, but the magnetic powder particle size used is ≤1μm, and the magnetic permeability is low, which cannot meet the requirements of conventional inductance.
[0006] CN115565744A discloses a water-based magnetic slurry and its preparation method and application, wherein the water-based magnetic slurry includes magnetic powder, a binder and water; the binder includes any one of sodium carboxymethyl cellulose, carboxymethyl chitosan or sodium alginate or a combination of at least two thereof. The water-based magnetic slurry is in a free-flowing liquid state and has the characteristics of adjustable viscosity, so it is suitable for coating processes such as cast coating, screen printing and transfer printing. Moreover, since no organic solvent is added, no organic volatile substances will be generated during subsequent use, which is very friendly to the production environment and production equipment. At the same time, the water-based magnetic slurry can be cured at a lower temperature, and the cured product has a higher magnetic permeability and a lower dielectric loss, and can be applied to the field of microelectronics, but the magnetic permeability and dielectric loss performance still need to be further improved.
[0007] Therefore, it is necessary to develop a magnetic slurry that can solve the problems of uneven magnetic powder and inductance cracking, and has good insulation and high magnetic permeability. Summary of the invention
[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a magnetic slurry and a preparation method and application thereof. The product made from the magnetic slurry has high magnetic permeability and low dielectric loss performance, good insulation, high resistance and can operate at a voltage of 300V, and can be used for encapsulating electronic components without pressing and molding.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a magnetic slurry, the magnetic slurry comprising a combination of an organic-inorganic composite insulation-coated iron-based alloy powder, a liquid resin, and a diluent;
[0011] The raw materials for preparing the organic-inorganic composite insulation-coated iron-based alloy powder include iron-based alloy powder, surfactant, inorganic insulating agent and organic coating resin.
[0012] In the present invention, the organic-inorganic composite insulation coated iron-based alloy powder is prepared by surface insulation coating of the iron-based alloy powder with an inorganic insulating agent, a surfactant and an organic coating resin, so that the resistance is improved. The magnetic slurry formed by the organic-inorganic composite insulation coated iron-based alloy powder and the liquid resin and the diluent has excellent fluidity and can be used for encapsulating electronic components without compression molding, solving the problems of uneven distribution of magnetic powder and inductance cracking during the molding curing process. The product prepared by the magnetic slurry has high magnetic permeability and low dielectric loss performance, good insulation, high resistance, and can work at a voltage of 300V. The magnetic slurry is easy to cure and is suitable for large-scale mass production.
[0013] Preferably, the iron-based alloy powder includes a first iron-based alloy powder, a second iron-based alloy powder, a third iron-based alloy powder and a fourth iron-based alloy powder.
[0014] Preferably, the D50 particle size of the first iron-based alloy powder is 40-50 μm, for example, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm or 49 μm.
[0015] Preferably, the D50 particle size of the second iron-based alloy powder is 10-20 μm, for example, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or 19 μm.
[0016] Preferably, the D50 particle size of the third iron-based alloy powder is 1-2 μm, for example, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm or 1.9 μm.
[0017] Preferably, the D50 particle size of the fourth iron-based alloy powder is 0.5-1 μm, for example, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm or 0.95 μm.
[0018] In the present invention, the grading of iron-based alloy powders with different particle sizes is beneficial to improving the magnetic permeability of the magnetic slurry, thereby solving the problem of low magnetic permeability.
[0019] Preferably, based on 100 parts by weight of the total iron-based alloy powder, the weight of the first iron-based alloy powder is 65 to 75 parts (e.g., 66, 67, 68, 69, 70, 71, 72, 73 or 74 parts, etc.), and the weight of the second iron-based alloy powder is 15 to 25 parts (e.g., 16, 17, 18, 19, 20, 21, 22, 23, 24, etc.). 3 or 24 parts, etc.), the weight number of the third iron-based alloy powder is 5 to 10 parts (for example, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts or 9.5 parts, etc.), and the weight number of the fourth iron-based alloy powder is 2 to 4 parts (for example, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3.0 parts, 3.2 parts, 3.4 parts, 3.6 parts or 3.8 parts, etc.).
[0020] Preferably, the first iron-based alloy powder, the second iron-based alloy powder, the third iron-based alloy powder and the fourth iron-based alloy powder each independently include any one of iron-silicon-chromium powder, sendustine-aluminum powder, carbonyl iron powder or ferrite powder, or a combination of at least two thereof.
[0021] Preferably, the first iron-based alloy powder includes iron-silicon-chromium powder, and the second iron-based alloy powder includes iron-silicon-aluminum powder.
[0022] Preferably, the first iron-based alloy powder includes sendustine-aluminum powder, and the second iron-based alloy powder includes sendustine-chromium powder.
[0023] Preferably, the third iron-based alloy powder includes carbonyl iron powder.
[0024] Preferably, the fourth iron-based alloy powder includes ferrite powder.
[0025] Preferably, the surfactant is any one of tetraethyl silicate, tetrabutyl titanate or a silane coupling agent, or a combination of at least two thereof.
[0026] Preferably, the silane coupling agent includes γ-aminopropyltriethoxysilane (KH550) and / or γ-glycidyloxypropyltrimethoxysilane (KH560).
[0027] Preferably, the inorganic insulating agent includes any one of phosphoric acid, aluminum dihydrogen phosphate or sulfuric acid, or a combination of at least two thereof.
[0028] Preferably, the organic coating resin includes any one of epoxy resin, phenolic resin or polyester resin, or a combination of at least two of them.
[0029] Exemplarily, the epoxy resin includes any one or at least two of epoxy resin E51, epoxy resin E44 or epoxy resin TDE80.
[0030] Preferably, the mass ratio of the surfactant to the iron-based alloy powder is (0.8-1.2):100, for example, 0.85:100, 0.9:100, 0.95:100, 1.00:100, 1.05:100, 1.10:100 or 1.15:100, etc.
[0031] Preferably, the mass ratio of the inorganic insulating agent to the iron-based alloy powder is (0.1-0.5):100, for example, 0.15:100, 0.2:100, 0.25:100, 0.3:100, 0.35:100, 0.4:100 or 0.45:100, etc.
[0032] Preferably, the mass ratio of the organic coating resin to the iron-based alloy powder is (0.1-0.5):100, for example, 0.15:100, 0.2:100, 0.25:100, 0.3:100, 0.35:100, 0.4:100 or 0.45:100, etc.
[0033] Preferably, the liquid resin comprises epoxy resin.
[0034] Preferably, the diluent includes any one of neopentyl glycol diglycidyl ether, benzyl alcohol or butyl glycidyl ether, or a combination of at least two thereof.
[0035] Preferably, the magnetic slurry includes the following components in parts by weight: 70 to 80 parts (for example, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts or 79 parts, etc.) of organic-inorganic composite insulation coated iron-based alloy powder, 10 to 15 parts (for example, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts or 14.5 parts, etc.) of liquid resin and 10 to 15 parts (for example, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts or 14.5 parts, etc.) of diluent.
[0036] In a second aspect, the present invention provides a method for preparing the magnetic slurry as described in the first aspect, the preparation method comprising the following steps:
[0037] (1) mixing an iron-based alloy powder and an inorganic insulating agent to obtain an inorganic insulating-coated iron-based alloy powder;
[0038] (2) mixing the inorganic insulation-coated iron-based alloy powder obtained in step (1) with a surfactant to obtain a surfactant-coated iron-based alloy powder;
[0039] (3) mixing the surfactant-coated iron-based alloy powder obtained in step (2) with an organic coating resin to obtain an organic-inorganic composite insulation-coated iron-based alloy powder;
[0040] (4) Mixing the organic-inorganic composite insulation-coated iron-based alloy powder obtained in step (3), liquid resin and diluent to obtain the magnetic slurry.
[0041] Preferably, the step (3) specifically comprises the following steps: dissolving the organic coating resin in a solvent, then mixing it with the surfactant-coated iron-based alloy powder obtained in step (2), and drying to obtain an organic-inorganic composite insulation-coated iron-based alloy powder.
[0042] Preferably, the solvent comprises ethanol.
[0043] Preferably, the mass ratio of the coating resin to the solvent is 1:(4-8), for example, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7 or 1:7.5, etc.
[0044] In a third aspect, the present invention provides an inductor magnetic sheet, wherein the inductor magnetic sheet is made of the magnetic slurry as described in the first aspect.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] In the present invention, the organic-inorganic composite insulation coated iron-based alloy powder is prepared by surface insulation coating of the iron-based alloy powder with an inorganic insulating agent, a surfactant and an organic coating resin, so that the resistance is improved. The magnetic slurry formed by the organic-inorganic composite insulation coated iron-based alloy powder, liquid resin and diluent has excellent fluidity and can be used for potting electronic components without compression molding, solving the problems of uneven distribution of magnetic powder and inductance cracking during the molding curing process. The product prepared by the magnetic slurry has high magnetic permeability and low dielectric loss performance, good insulation, high resistance, and can work at a voltage of 300V. The magnetic slurry is easy to cure and is suitable for large-scale mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 A front view of the inductor magnetic sheet provided in Example 1;
[0048] Figure 2 This is a side view of the inductor magnetic sheet provided in Example 1. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Example 1
[0051] The present embodiment provides a magnetic slurry and a preparation method thereof and an inductor magnetic sheet, wherein the magnetic slurry comprises the following components by weight: 80 parts of iron-based alloy powder coated with organic-inorganic composite insulation, 10 parts of liquid resin (epoxy resin TT300, manufactured by Jiangsu Taitel) and 10 parts of diluent (neopentyl glycol diglycidyl ether);
[0052] The raw materials for preparing the above-mentioned organic-inorganic composite insulation coated iron-based alloy powder include, by weight, 100 parts of iron-based alloy powder, 1 part of surfactant (glycidyl ether oxypropyl trimethoxy silane), 0.1 part of inorganic insulating agent (phosphoric acid) and 0.1 part of organic coating resin (Phoenix brand epoxy resin E51).
[0053] The above-mentioned iron-based alloy powder includes the following components in parts by weight: 70 parts of iron silicon chromium powder (D50 particle size is 45μm), 20 parts of sendustine powder (D50 particle size is 15μm), 7 parts of carbonyl iron powder (D50 particle size is 1.5μm) and 3 parts of ferrite powder (D50 particle size is 0.7μm, manganese-zinc ferrite).
[0054] The preparation method of the magnetic slurry comprises the following steps:
[0055] (1) Mixing iron silicon chromium powder, iron silicon aluminum powder, ferrite powder and carbonyl iron powder to form an iron-based alloy powder, adding a solution prepared by an inorganic insulating agent and ethanol, stirring and mixing, the mass ratio of the iron-based alloy powder, ethanol and inorganic insulating agent is 100:15:0.1, and then putting it into an oven at 80° C. for 1 hour to obtain an inorganic insulating coated iron-based alloy powder;
[0056] (2) dissolving a surfactant in ethanol and water and mechanically stirring for 1 hour, wherein the mass ratio of surfactant: water: ethanol is 1:10:40, adding the inorganic insulation coated iron-based alloy powder obtained in step (1), stirring evenly, filtering, and drying in an oven at 80° C. for 6 hours to obtain the surfactant coated iron-based alloy powder;
[0057] (3) dissolving the organic coating resin in ethanol, wherein the mass ratio of the organic coating resin to ethanol is 1:4, and then stirring and mixing with the surfactant-coated iron-based alloy powder obtained in step (2), placing in an oven at 160° C. and drying for 1 h, to obtain an organic-inorganic composite insulation-coated iron-based alloy powder;
[0058] (4) The organic-inorganic composite insulation-coated iron-based alloy powder, liquid resin and diluent prepared in step (3) are stirred and mixed, and then mixed evenly by a three-roll mill to obtain the magnetic slurry.
[0059] The magnetic slurry was placed in a vacuum oven for 5 minutes to remove bubbles, then poured into a mold, heated and cured at 160°C for 1 hour to obtain an inductor magnetic sheet. The inductor magnetic sheet was a hollow cylinder with an outer diameter of 17 mm, an inner diameter of 9 mm, and a height of 4 mm. Figure 1 and Figure 2 shown.
[0060] Example 2
[0061] This embodiment provides a magnetic slurry and a preparation method thereof and an inductor magnetic sheet, wherein the magnetic slurry comprises the following components by weight: 70 parts of organic-inorganic composite insulation-coated iron-based alloy powder, 15 parts of liquid resin (epoxy resin TT300, manufactured by Jiangsu Taitel) and 15 parts of diluent (benzyl alcohol);
[0062] The raw materials for preparing the above-mentioned organic-inorganic composite insulation coated iron-based alloy powder include, by weight, 100 parts of iron-based alloy powder, 1 part of surfactant (glycidyl ether oxypropyl trimethoxy silane), 0.3 parts of inorganic insulating agent (aluminum dihydrogen phosphate) and 0.3 parts of organic coating resin (Phoenix brand epoxy resin E51).
[0063] The above-mentioned iron-based alloy powder includes the following components in parts by weight: 70 parts of iron silicon chromium powder (D50 particle size is 50μm), 20 parts of sendustine powder (D50 particle size is 20μm), 7 parts of carbonyl iron powder (D50 particle size is 2μm) and 3 parts of ferrite powder (D50 particle size is 1μm, manganese zinc ferrite).
[0064] The preparation method of the magnetic slurry comprises the following steps:
[0065] (1) Mixing iron silicon chromium powder, iron silicon aluminum powder, ferrite powder and carbonyl iron powder to form iron-based alloy powder, adding a solution prepared by an inorganic insulating agent and ethanol, stirring and mixing, the mass ratio of the iron-based alloy powder, ethanol and inorganic insulating agent is 100:15:0.3, and then putting it into an oven at 80° C. for drying for 1 hour to obtain an inorganic insulating coated iron-based alloy powder;
[0066] (2) dissolving a surfactant in ethanol and water and mechanically stirring for 1 hour, wherein the mass ratio of surfactant: water: ethanol is 1:10:40, adding the inorganic insulation coated iron-based alloy powder obtained in step (1), stirring evenly, filtering, and drying in an oven at 80° C. for 6 hours to obtain the surfactant coated iron-based alloy powder;
[0067] (3) dissolving the organic coating resin in a solvent (ethanol) at a mass ratio of 1:8, and then stirring and mixing with the surfactant-coated iron-based alloy powder obtained in step (2), and drying in an oven at 160° C. for 1 h to obtain an organic-inorganic composite insulation-coated iron-based alloy powder;
[0068] (4) The organic-inorganic composite insulation-coated iron-based alloy powder, liquid resin and diluent prepared in step (3) are stirred and mixed, and then mixed evenly by a three-roll mill to obtain the magnetic slurry.
[0069] The magnetic slurry was placed in a vacuum oven for 5 minutes to remove bubbles, then poured into a mold, heated and cured at 160° C. for 1 hour to obtain an inductor magnetic sheet, which was a hollow cylinder with an outer diameter of 17 mm, an inner diameter of 9 mm, and a height of 4 mm.
[0070] Example 3
[0071] This embodiment provides a magnetic slurry and a preparation method thereof and an inductor magnetic sheet, wherein the magnetic slurry comprises the following components by weight: 75 parts of iron-based alloy powder coated with organic-inorganic composite insulation, 12.5 parts of liquid resin (epoxy resin TT300, manufactured by Jiangsu Taitel) and 12.5 parts of diluent (benzyl alcohol);
[0072] The raw materials for preparing the above-mentioned organic-inorganic composite insulation coated iron-based alloy powder include, by weight, 100 parts of iron-based alloy powder, 1 part of surfactant (tetraethyl silicate), 0.5 parts of inorganic insulating agent (sulfuric acid) and 0.5 parts of organic coating resin (Phoenix brand epoxy resin E51).
[0073] The above-mentioned iron-based alloy powder includes the following components in parts by weight: 70 parts of iron silicon chromium powder (D50 particle size is 40μm), 20 parts of sendustine powder (D50 particle size is 10μm), 7 parts of carbonyl iron powder (D50 particle size is 1μm) and 3 parts of ferrite powder (D50 particle size is 0.5μm, manganese zinc ferrite).
[0074] The preparation method of the magnetic slurry comprises the following steps:
[0075] (1) Mixing iron silicon chromium powder, iron silicon aluminum powder, ferrite powder and carbonyl iron powder to form iron-based alloy powder, adding a solution prepared by an inorganic insulating agent and ethanol, stirring and mixing, the mass ratio of the iron-based alloy powder, ethanol and inorganic insulating agent is 100:15:0.5, and then putting it into an oven at 80° C. for drying for 1 hour to obtain an inorganic insulating coated iron-based alloy powder;
[0076] (2) dissolving a surfactant in ethanol and water and mechanically stirring for 1 hour, wherein the mass ratio of surfactant: water: ethanol is 1:10:40, adding the inorganic insulation coated iron-based alloy powder obtained in step (1), stirring evenly, filtering, and drying in an oven at 80° C. for 6 hours to obtain the surfactant coated iron-based alloy powder;
[0077] (3) dissolving the organic coating resin in a solvent (ethanol) at a mass ratio of 1:8, and then stirring and mixing with the surfactant-coated iron-based alloy powder obtained in step (2), and drying in an oven at 160° C. for 1 h to obtain an organic-inorganic composite insulation-coated iron-based alloy powder;
[0078] (4) The organic-inorganic composite insulation-coated iron-based alloy powder, liquid resin and diluent prepared in step (3) are stirred and mixed, and then mixed evenly by a three-roll mill to obtain the magnetic slurry.
[0079] The magnetic slurry was placed in a vacuum oven for 5 minutes to remove bubbles, then poured into a mold, heated and cured at 160° C. for 1 hour to obtain an inductor magnetic sheet, which was a hollow cylinder with an outer diameter of 17 mm, an inner diameter of 9 mm, and a height of 4 mm.
[0080] Example 4
[0081] This embodiment provides a magnetic slurry, a preparation method thereof, and an inductor magnetic sheet. The only difference between this embodiment and Embodiment 1 is that the organic coating resin (Phoenix brand epoxy resin E51) is replaced with an organic coating resin of the same quality (phenolic resin F51, manufactured by Yoshida Chemical), and other conditions are the same as those in Embodiment 1.
[0082] Example 5
[0083] This embodiment provides a magnetic slurry, a preparation method thereof, and an inductor magnetic sheet. The difference between this embodiment and the first embodiment is that the weight fraction of the inorganic coating agent (phosphoric acid) is adjusted to 1 part, and other conditions are the same as those of the first embodiment.
[0084] Example 6
[0085] This embodiment provides a magnetic slurry, a preparation method thereof, and an inductor magnetic sheet. The difference between this embodiment and the first embodiment is that the weight fraction of the organic coating resin (Phoenix brand epoxy resin E51) is adjusted to 1 part, and other conditions are the same as those of the first embodiment.
[0086] Example 7
[0087] The present embodiment provides a magnetic slurry, a preparation method thereof and an inductor magnetic sheet. The only difference between the present embodiment and the embodiment 1 is that the iron-based alloy powder includes the following components by weight: 90 parts of sendustine powder (D50 particle size is 15 μm), 7 parts of carbonyl iron powder (D50 particle size is 1.5 μm) and 3 parts of ferrite powder (D50 particle size is 0.7 μm, manganese-zinc ferrite). Other conditions are the same as those in the embodiment 1.
[0088] Example 8
[0089] The present embodiment provides a magnetic slurry, a preparation method thereof and an inductor magnetic sheet. The only difference between the present embodiment and the embodiment 1 is that the iron-based alloy powder includes the following components in parts by weight: 70 parts of iron silicon chromium powder (D50 particle size is 45 μm), 20 parts of sendustine aluminum powder (D50 particle size is 15 μm), and 10 parts of carbonyl iron powder (D50 particle size is 1.5 μm). Other conditions are the same as those in the embodiment 1.
[0090] Comparative Example 1
[0091] This comparative example provides a magnetic slurry, a preparation method thereof, and an inductor magnetic sheet, which differs from Example 1 only in that no organic coating resin and surfactant are added, the preparation method of the magnetic slurry does not include steps (2) and (3), and the organic-inorganic composite insulation-coated iron-based alloy powder in step (4) is replaced by the inorganic insulation-coated iron-based alloy powder obtained in step (1), and other conditions are the same as those in Example 1.
[0092] Comparative Example 2
[0093] This comparative example provides a magnetic slurry, a preparation method thereof, and an inductor magnetic sheet, which differs from Example 1 only in that no inorganic insulating agent is added, the preparation method of the magnetic slurry does not include step (1), and the iron-based alloy powder coated with inorganic insulation in step (2) is replaced with iron-based alloy powder, and other conditions are the same as those in Example 1.
[0094] The following performance tests were performed on the inductor magnetic sheets provided in the above embodiments and comparative examples.
[0095] (1) Magnetic permeability: Wind the annular inductor magnetic sheet with enameled copper wire for 26 turns and test the magnetic permeability at 0 A and 100 kHz.
[0096] (2) Dielectric loss: The dielectric loss is tested by winding the annular inductor magnetic plate with 18 turns of bifilar wire at an electric field strength of 20 mT and a frequency of 1 MHz.
[0097] (3) Resistance: The resistance is tested under the conditions of voltage 300 V and discharge time 6 s.
[0098] The test results are shown in Table 1 below.
[0099] Table 1
[0100]
[0101] In Table 1, “ / ” means the value is lower and was not measured.
[0102] From the content of Table 1, it can be seen that the magnetic permeability of the inductor magnetic sheet provided in Examples 1-8 is 11.5-13.5, and the dielectric loss is 473-585 mW / cm 3 , resistance is 8~60GΩ, has high magnetic permeability and low dielectric loss, has high resistance and can work at 300V voltage.
[0103] Compared with Example 1, if the mass ratio of the inorganic insulating agent to the iron-based alloy powder is too high, and the weight fraction of the inorganic insulating agent is too much (Example 5), the magnetic permeability of the prepared inductor magnetic sheet is significantly reduced, which is not conducive to industrial application; if the mass ratio of the coating resin to the iron-based alloy powder is too high (Example 6), the magnetic permeability of the prepared inductor magnetic sheet will also decrease. It can be seen that the performance of the magnetic slurry prepared by controlling the mass ratio of the coating resin to the iron-based alloy powder within a specific range is better.
[0104] Compared with Example 1, if large-particle iron-silicon-chromium powder is not added (Example 7) or small-particle ferrite powder is not added (Example 8), the magnetic permeability of the prepared inductor magnetic sheet will decrease, and the grading cannot reach an ideal state. It can be seen that the present invention uses grading of four iron-based alloy powders with different particle sizes to prepare a magnetic slurry with better performance.
[0105] Compared with Example 1, if no organic coating resin and surfactant are added (Comparative Example 1) or no inorganic insulating agent is added (Comparative Example 2), the prepared inductor magnetic sheet has low resistance and low withstand voltage. It can be seen that the insulation effect of only using organic materials to coat iron-based alloy powder or only using inorganic insulating agents to coat iron-based alloy powder is poor, and the inductor magnetic sheet prepared by using organic coating resin, surfactant and inorganic insulating agent to coat iron-based alloy powder has better performance.
[0106] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A magnetic slurry, characterized in that: The magnetic slurry comprises a combination of organic-inorganic composite insulation-coated iron-based alloy powder, liquid resin and diluent; The raw materials for preparing the organic-inorganic composite insulation-coated iron-based alloy powder include iron-based alloy powder, surfactant, inorganic insulating agent and organic coating resin.
2. The magnetic slurry according to claim 1, characterized in that: The iron-based alloy powder includes a first iron-based alloy powder, a second iron-based alloy powder, a third iron-based alloy powder and a fourth iron-based alloy powder; Preferably, the D50 particle size of the first iron-based alloy powder is 40-50 μm; Preferably, the D50 particle size of the second iron-based alloy powder is 10 to 20 μm; Preferably, the D50 particle size of the third iron-based alloy powder is 1 to 2 μm; Preferably, the D50 particle size of the fourth iron-based alloy powder is 0.5-1 μm; Preferably, based on 100 parts by weight of the total iron-based alloy powder, the weight of the first iron-based alloy powder is 65 to 75 parts, the weight of the second iron-based alloy powder is 15 to 25 parts, the weight of the third iron-based alloy powder is 5 to 10 parts, and the weight of the fourth iron-based alloy powder is 2 to 4 parts; Preferably, the first iron-based alloy powder, the second iron-based alloy powder, the third iron-based alloy powder and the fourth iron-based alloy powder each independently include any one of iron-silicon-chromium powder, sendustine-aluminum powder, carbonyl iron powder or ferrite powder, or a combination of at least two thereof.
3. The magnetic slurry according to claim 2, characterized in that: The first iron-based alloy powder includes iron-silicon-chromium powder, and the second iron-based alloy powder includes iron-silicon-aluminum powder.
4. The magnetic slurry according to claim 2, characterized in that: The first iron-based alloy powder includes sendustine-aluminum powder, and the second iron-based alloy powder includes sendustine-chromium powder.
5. The magnetic slurry according to any one of claims 2 to 4, characterized in that: The third iron-based alloy powder includes carbonyl iron powder; Preferably, the fourth iron-based alloy powder includes ferrite powder.
6. The magnetic slurry according to any one of claims 1 to 5, characterized in that: The surfactant is any one of tetraethyl silicate, tetrabutyl titanate or a silane coupling agent, or a combination of at least two thereof; Preferably, the silane coupling agent includes γ-aminopropyltriethoxysilane and / or γ-glycidyloxypropyltrimethoxysilane; Preferably, the inorganic insulating agent includes any one of phosphoric acid, aluminum dihydrogen phosphate or sulfuric acid, or a combination of at least two thereof; Preferably, the organic coating resin includes any one of epoxy resin, phenolic resin or polyester resin, or a combination of at least two thereof; Preferably, the mass ratio of the surfactant to the iron-based alloy powder is (0.8-1.2):100; Preferably, the mass ratio of the inorganic insulating agent to the iron-based alloy powder is (0.1-0.5):100; Preferably, the mass ratio of the organic coating resin to the iron-based alloy powder is (0.1-0.5):
100.
7. The magnetic slurry according to any one of claims 1 to 6, characterized in that: The liquid resin includes epoxy resin; Preferably, the diluent comprises any one or a combination of at least two of neopentyl glycol diglycidyl ether, benzyl alcohol or butyl glycidyl ether; Preferably, the magnetic slurry comprises the following components in parts by weight: 70 to 80 parts of organic-inorganic composite insulation-coated iron-based alloy powder, 10 to 15 parts of liquid resin and 10 to 15 parts of diluent.
8. A method for preparing a magnetic slurry according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing an iron-based alloy powder and an inorganic insulating agent to obtain an inorganic insulating-coated iron-based alloy powder; (2) mixing the inorganic insulation-coated iron-based alloy powder obtained in step (1) with a surfactant to obtain a surfactant-coated iron-based alloy powder; (3) mixing the surfactant-coated iron-based alloy powder obtained in step (2) with an organic coating resin to obtain an organic-inorganic composite insulation-coated iron-based alloy powder; (4) Mixing the organic-inorganic composite insulation-coated iron-based alloy powder obtained in step (3), liquid resin and diluent to obtain the magnetic slurry.
9. The preparation method according to claim 8, characterized in that: The step (3) specifically comprises the following steps: dissolving the organic coating resin in a solvent, then mixing it with the surfactant-coated iron-based alloy powder obtained in step (2), and drying it to obtain an organic-inorganic composite insulation-coated iron-based alloy powder; Preferably, the solvent comprises ethanol; Preferably, the mass ratio of the coating resin to the solvent is 1:(4-8).
10. An inductor magnetic sheet, characterized in that: The inductor magnetic sheet is made of the magnetic slurry as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Magnetic slurry and preparation and application thereof
CN105647128A